2015
DOI: 10.5717/jenb.2015.19.2.49
|View full text |Cite
|
Sign up to set email alerts
|

The COL5A1 genotype is associated with range of motion

Abstract: Seung-Taek Lim, Chang-Sun Kim, Woo-Nam Kim and Seok-Ki Min. The COL5A1 genotype is associated with range of motion. JENB., Vol. 19, No. 2, pp.49-53, 2015 [Purpose] The aim of our study was to investigate the association between COL5A1 genotype and Range of Motion as measured by the passive straight leg raise (SLR) and whole body join laxity (WBJL) in Asian population.[Methods] One hundred and seventy seven participants including Korean and Japanese college students (male = 109, female = 68) participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
2
2
Order By: Relevance
“…The study showed that there is an association between COL5a1 rs12722 and tendon pathology in the rotator cuff, not however for COL11a1 rs3753841, COL11a1 rs1676486, or COL11a2 rs1799907. The SNP COL5a1 rs12722 genotype frequency in our study was very different from the data found in Korean college students (53.8% CC, 40.7% CT, and 4%) 34 and in the Japanese population (76% CC and 24% TT + CT). 35 The data obtained by Bertuzzi et al 36 in a group of young, active Brazilian participants showed a distribution more similar to ours (16% CC, 56% CT, and 28% TT), although with higher incidence of genotype CC in detriment to TT, a finding consistent with the study conducted by Brown et al 19 (19.5% CC, 47.4% CT, and 33.1% TT).…”
Section: Discussioncontrasting
confidence: 99%
“…The study showed that there is an association between COL5a1 rs12722 and tendon pathology in the rotator cuff, not however for COL11a1 rs3753841, COL11a1 rs1676486, or COL11a2 rs1799907. The SNP COL5a1 rs12722 genotype frequency in our study was very different from the data found in Korean college students (53.8% CC, 40.7% CT, and 4%) 34 and in the Japanese population (76% CC and 24% TT + CT). 35 The data obtained by Bertuzzi et al 36 in a group of young, active Brazilian participants showed a distribution more similar to ours (16% CC, 56% CT, and 28% TT), although with higher incidence of genotype CC in detriment to TT, a finding consistent with the study conducted by Brown et al 19 (19.5% CC, 47.4% CT, and 33.1% TT).…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of our knowledge, four studies have attempted to identify the association between the COL5A1 rs12722 polymorphism and joint flexibility (10)(11)(12)33). Of these, three have indicated a potential association (10)(11)(12), which seems to be inconsistent with the present results. However, careful attention should be paid when interpreting the previous findings.…”
Section: Discussioncontrasting
confidence: 95%
“…To the best of our knowledge, four studies have attempted to identify the association between the COL5A1 rs12722 polymorphism and joint flexibility (10)(11)(12)33). Of these, three have indicated a potential association (10)(11)(12), which seems to be inconsistent with the present results. However, careful attention should be paid when interpreting the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…The collagen type V α1 chain gene (COL5A1) has been proposed as a candidate gene whose variants affect not only muscle injury per se but also passive muscle stiffness and joint flexibility (9). Several studies examining the association of the C-to-T polymorphism (rs12722) in the 3′-untranslated region (UTR) of the COL5A1 with ROM in sit-and-reach (SR) or passive straight-leg-raise (PSLR) tests (10)(11)(12) suggest that this polymorphism could be a factor affecting ROM. Although the ROMs in SR and PSLR tests are multifactorial, passive muscle stiffness has been proposed to be a major contributor to the ROM of normal joints (13,14).…”
Section: Introductionmentioning
confidence: 99%